SKEMA INTERAKSI SOSIAL ETNIS CINA-JAWA KOTA SURAKARTA - Verbena Ayuningsih Purbasari; Suharno Suharno (Universitas Andalas, 2019)
Surakarta has a multiethnic and multicultural society. There have been long conflicts that led to forms of discrimination and violence against ethnic Chinese in Surakarta. This conflict resulted in deep trauma for the Surakarta society. Conflict reconciliation is needed so that there is no gap between the society. One of the efforts made is to carry out social interactions. The purpose of this study was to create a scheme of forms of social interaction spread across several fields. This article was prepared using a library study method where the data obtained came from various books, journals, and theses. The results show that the interaction of Chinese and Javanese in Surakarta can be made into a scheme grouped in 8 fields, such as language, education, economics, religion, community activities, arts, marriage, and culture